Semaglutide for the treatment of antipsychotic-associated weight gain in patients not responding to metformin - a case series - Femin Prasad; Riddhita De; Vittal Korann; Araba F. Chintoh; Gary Remington; Bjørn H. Ebdrup; Dan Siskind; Filip Krag Knop; Tina Vilsbøll; Anders Fink-Jensen; Margaret K. Hahn; Sri Mahavir Agarwal (SAGE Publishing, 2023)
Metformin is the currently accepted first-line treatment for antipsychotic-associated weight gain (AAWG). However, not all patients benefit from metformin. Glucagon-like peptide-1 receptor agonists (GLP1-RA) have shown promise in the management of obesity in the general population, with preliminary evidence supporting efficacy in AAWG. Semaglutide is a weekly injectable GLP-1RA which received recent approval for obesity management and noted superiority over other GLP-1RAs. This study explored the efficacy and tolerability of semaglutide in AAWG among individuals with severe mental illness. A retrospective chart review of patients treated with semaglutide in the Metabolic Clinic at the Center for Addiction and Mental Health (CAMH) between 2019 and 2021 was conducted. Patients failing a trial of metformin (<5% weight loss or continuing to meet criteria for metabolic syndrome) after 3 months at the maximum tolerated dose (1500-2000 mg/day) were initiated on semaglutide up to 2 mg/week. The primary outcome measure was a change in weight at 3, 6, and 12 months. Twelve patients on weekly semaglutide injections of 0.71 ± 0.47 mg/week were included in the analysis. About 50% were female; the average age was 36.09 ± 13.32 years. At baseline, mean weight was 111.4 ± 31.7 kg, BMI was 36.7 ± 8.2 kg/m 2 , with a mean waist circumference of 118.1 ± 19.3 cm. A weight loss of 4.56 ± 3.15 kg ( p  < 0.001), 5.16 ± 6.27 kg ( p  = 0.04) and 8.67 ± 9 kg ( p  = 0.04) was seen at 3, 6, and 12 months, respectively, after initiation of semaglutide with relatively well-tolerated side-effects. Initial evidence from our real-world clinical setting suggests that semaglutide may be effective in reducing AAWG in patients not responding to metformin. Randomized control trials investigating semaglutide for AAWG are needed to corroborate these findings.